Immunogenicity Evaluation of N‑Glycans Recognized by HIV Broadly Neutralizing Antibodies - Shivatare, Sachin S; Cheng, Ting-Jen Rachel; Cheng, Yang-Yu; Shivatare, Vidya S; Tsai, Tsung-I; Chuang, Hong-Yang; Wu, Chung-Yi; Wong, Chi-Huey (ACS chemical biology, 2021)
While the improved treatment of human immunodeficiency virus type 1 (HIV-1) infection is available, the development of an effective and safe prophylactic vaccine against HIV-1 is still an unrealized goal. Encouragingly, the discovery of broadly neutralizing antibodies (bNAbs) from HIV-1 positive patients that are capable of neutralizing a broad spectrum of HIV-1 isolates of various clades has accelerated the progress of vaccine development in the past few years. Some of these bNAbs recognize the N-glycans on the viral surface gp120 glycoprotein. We have been interested in using the glycan epitopes recognized by bNAbs for the development of vaccines to elicit bNAb-like antibodies with broadly neutralizing activities. Toward this goal, we have identified novel hybrid-type structures with subnanomolar avidity toward several bNAbs including PG16, PGT121, PGT128-3C, 2G12, VRC13, VRC-PG05, VRC26.25, VRC26.09, PGDM1400, 35O22, and 10-1074. Here, we report the immunogenicity evaluation of a novel hybrid glycan conjugated to carrier DTCRM197, a nontoxic mutant of the diphtheria toxin, for immunization in mice. Our results indicated that the IgG response was mainly against the chitobiose motif with nonspecific binding to a panel of N-glycans with reducing end GlcNAc–GlcNAc (chitobiose) printed on the glass slides. However, the IgM response was mainly toward the reducing end GlcNAc moiety. We further used the glycoconjugates of Man3GlcNAc2, Man5GlcNAc2, and Man9GlcNAc2 glycans for immunization, and a similar specificity pattern was observed. These findings suggest that the immunogenicity of chitobiose may interfere with the outcome of N-glycan-based vaccines, and modification may be necessary to increase the immunogenicity of the entire N-glycan epitope.